2017
DOI: 10.1038/s41598-017-15126-w
|View full text |Cite
|
Sign up to set email alerts
|

Entrainment of Voluntary Movement to Undetected Auditory Regularities

Abstract: In physics “entrainment” refers to the synchronization of two coupled oscillators with similar fundamental frequencies. In behavioral science, entrainment refers to the tendency of humans to synchronize their movements with rhythmic stimuli. Here, we asked whether human subjects performing a tapping task would entrain their tapping to an undetected auditory rhythm surreptitiously introduced in the guise of ambient background noise in the room. Subjects performed two different tasks, one in which they tapped th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…In other words, at least for most individuals the SMT/PPT seem to fall within the 'sweet spot' for optimal continuation tapping, and when attempting to perform memory-based tapping for faster/slower rhythms, de-facto tapping rates drifted towards producing rhythms in the vicinity of one's SMT/PPT. This pattern is consistent with the notion that individuals have a preferred range of rhythms, within which complex rhythmic behavior and perceptual sensitivity is optimal (McPherson et al, 2018;Phillips-Silver et al, 2011;Scheurich et al, 2018;Schurger et al, 2017;Zamm et al, 2015Zamm et al, , 2018, and extends these findings to memory-based continuation tapping. Interestingly, similar U-shape patterns were observed for the ADHD and control groups around their SMT/PPTs, eventhough the SMT/PPT rhythms themselves were slightly faster in the ADHD groups.…”
Section: Generalizability Of Preferred Motor and Auditory Perceptual Rhythmssupporting
confidence: 88%
“…In other words, at least for most individuals the SMT/PPT seem to fall within the 'sweet spot' for optimal continuation tapping, and when attempting to perform memory-based tapping for faster/slower rhythms, de-facto tapping rates drifted towards producing rhythms in the vicinity of one's SMT/PPT. This pattern is consistent with the notion that individuals have a preferred range of rhythms, within which complex rhythmic behavior and perceptual sensitivity is optimal (McPherson et al, 2018;Phillips-Silver et al, 2011;Scheurich et al, 2018;Schurger et al, 2017;Zamm et al, 2015Zamm et al, , 2018, and extends these findings to memory-based continuation tapping. Interestingly, similar U-shape patterns were observed for the ADHD and control groups around their SMT/PPTs, eventhough the SMT/PPT rhythms themselves were slightly faster in the ADHD groups.…”
Section: Generalizability Of Preferred Motor and Auditory Perceptual Rhythmssupporting
confidence: 88%
“…The present findings support the view that auditory stimuli, particularly naturalistic sound, has a substantial contribution to dynamic modulations of movement. That recent work has shown that undetected auditory cues can have influences on voluntary movement (tapping speed and single taps following delay of the participant's choosing), suggesting that decisions to act are amenable to unnoticed sensory influences from the surrounding environment (Schurger et al, 2017).…”
Section: Interim Summarymentioning
confidence: 99%
“…However, oscillatory activity does not even have to reach the level of conscious awareness to affect cognition. Experiments conducted by Schurger et al (2017) have shown that undetected auditory regularities entrain voluntary movement. These and related phenomena JOLMA e-ISSN 2723-9640 1, 2, 2020, 195-214 206 appear to be part of a shared mechanism: the rhythmic entrainment of slow cortical oscillations to the temporal structure of a stream of stimuli (Schroeder, Lakatos 2009).…”
Section: Environmental Rhythms and Cognitionmentioning
confidence: 99%